The Success of Introducing Electronic Medical Records Using the Delone and Mclean Method: A Study in Nine Primary Healthcare Facilities in Surabaya - Wahyuni, Titin; Sutha, Diah Wijayanti; Setiawan, Mohammad Yusuf (International Journal of Health and Information System, 2025)
Since 2022, primary healthcare facilities in Surabaya have adopted electronic medical records for patient admission services. However, an evaluation of the implementation of the program has never been conducted. Therefore, the objective of this study is to evaluate the efficacy of integrating electronic medical records in the admission department of basic healthcare institutions in Surabaya. The evaluation is performed utilizing the DeLone and McLean methodologies. The characteristics assessed in this study are system quality, information quality, service quality, usage, user happiness, and perceived net benefit.   The research was carried out using a descriptive approach and incidental sampling. The respondents of this study are nine admission officers from nine primary healthcare facilities in the city of Surabaya. The result of this study indicates that all variables are in good to excellent condition. The system quality is in excellent condition, with a rating of 55.56%. The information quality, use, and perceived net benefit are also excellent, with a rating of 66.67%. Meanwhile, service quality is at a satisfactory level of 66.67%, and user satisfaction is at a satisfactory level of 89%. The conclusion is that the implementation of electronic medical records has been highly successful, at 78%. It requires a step to implement to enhance the functionality of electronic medical records, including the incorporation of universal consent and the inclusion of patients' electronic signatures.